2013
DOI: 10.1037/a0035212
|View full text |Cite
|
Sign up to set email alerts
|

Mind the Gap in Mindfulness Research: A Comparative Account of the Leading Schools of Thought

Abstract: The literature on mindfulness has been dominated by the two leading schools of thought: one advanced by Langer and her colleagues the other developed by Kabat-Zinn and his associates. Curiously, the two strands of research have been running in parallel lines for more than 30 years, scarcely addressing each others' work, and with hardly any attempt to clarify the relationship between them. In view of this gap, this paper aims to systematically compare and contrast the two lines of research.The comparison betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
136
1
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 136 publications
(149 citation statements)
references
References 139 publications
(405 reference statements)
3
136
1
9
Order By: Relevance
“…Mindfulness is a practice of non-judgmental awareness of present moment experiences (Kabat-Zinn, 2005; see also Hart, Ivtzan, & Hart, 2013) that is inherently linked to greater wellbeing. There is a wealth of scientific literature spanning more than three decades demonstrating the beneficial impact mindfulness meditation has on health, wellbeing and psychological functioning in both clinical and non-clinical populations (for reviews see Keng, Smoski & Robins, 2011;Shapiro & Carlson, 2009;Baer, 2003;Dillbeck & Orme-Johnson, 1987).…”
Section: The Science Of Mindfulnessmentioning
confidence: 99%
“…Mindfulness is a practice of non-judgmental awareness of present moment experiences (Kabat-Zinn, 2005; see also Hart, Ivtzan, & Hart, 2013) that is inherently linked to greater wellbeing. There is a wealth of scientific literature spanning more than three decades demonstrating the beneficial impact mindfulness meditation has on health, wellbeing and psychological functioning in both clinical and non-clinical populations (for reviews see Keng, Smoski & Robins, 2011;Shapiro & Carlson, 2009;Baer, 2003;Dillbeck & Orme-Johnson, 1987).…”
Section: The Science Of Mindfulnessmentioning
confidence: 99%
“…Either of these two elements is capable of being heightened individually (Hart, Ivtzan, & Hart, 2013). However, despite theoretical and conceptual overlap , these drivers of human flourishing (or eudaimonic wellbeing) have only ever been applied separately.…”
Section: Introductionmentioning
confidence: 99%
“…This state of mind is an invitation for the practitioner to attend the full range of internal and external experiences with a non-judgemental stance (Hart, Ivtzan, & Hart, 2013). Studies have shown that mindfulness promotes both hedonic (Brown & Cordon, 2009) and eudaimonic wellbeing (Brown, Ryan, & Creswell, 2007).…”
Section: Introductionmentioning
confidence: 99%